Depressive symptoms among mothers with hospitalized children in South Asia and sub-Saharan Africa - Elshafei, A; Jemutai, J; Tickell, KD; Sukhtankar, P; Bhat, A; Molyneux, S; Berkley, JA; Walson, JL; Collins, PY (Elsevier, 2022)
Background: Poor maternal mental health during childhood hospitalization is associated with post-discharge child mortality. We aimed to establish if maternal PHQ-9 scores during hospitalization are associated with acute stressors or longer trends in mental health status.